Elements of metallurgy and engineering alloys - Campbell, F. C. (ASM International, 2008)
This practical reference provides thorough and systematic coverage on both basic metallurgy and the practical engineering aspects of metallic material selection and application.
Keywords: Metals.; Metallurgy.; Alloys.; elektronické knihy; electronic books